2012
DOI: 10.1039/c2cc32435k
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a ratiometric fluorescent probe with a large emission shift for the facile detection of Hg2+

Abstract: A new ratiometric and colorimetric fluorescent probe for the highly selective, sensitive and facile detection of Hg(2+) has been rationally developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…Chemical reactions that induced an extension of conjugation were recently used as a mechanism for the preparation of fluorogenic probes for Hg 2+ cations 23 and reactive oxygen species. 24 Also, 1 H NMR measurements were carried out in order to assess the dehydration mechanism for the color changes observed in the presence of Cr 3+ , Fe 3+ , Al 3+ , Ga 3+ , In 3+ and As 3+ .…”
Section: -21mentioning
confidence: 99%
“…Chemical reactions that induced an extension of conjugation were recently used as a mechanism for the preparation of fluorogenic probes for Hg 2+ cations 23 and reactive oxygen species. 24 Also, 1 H NMR measurements were carried out in order to assess the dehydration mechanism for the color changes observed in the presence of Cr 3+ , Fe 3+ , Al 3+ , Ga 3+ , In 3+ and As 3+ .…”
Section: -21mentioning
confidence: 99%
“…However, development of fluorescence ratiometric probes for metal ions has attracted a great deal of attention since they allow the measurement of emission intensities at two different wavelengths. Though many ratiometric chemosensors are reported [14][15][16][17], only a few sensors based on both colorimetric and ratiometric sensing have been reported for detection of Al 3 þ [18][19][20][21][22][23][24][25]. In this work, we designed a ratiometric probe (receptor 1) that displayed a selective colorimetric change and high ratiometric signals toward Al 3 þ among the other examined metal ions.…”
Section: Introductionmentioning
confidence: 96%
“…Mercury is one of the most toxic heavy metal elements [1,2]. Studies have shown that exposure to mercury, even at very low concentrations, leads to various diseases in the digestive system, the nervous system, and especially the neurological system, which makes detection of mercury ions (Hg 2+ ) an attractive research area in the biological field [3,4].…”
Section: Introductionmentioning
confidence: 99%